2021
DOI: 10.1021/acsanm.1c00853
|View full text |Cite
|
Sign up to set email alerts
|

Directed Ligand Exchange on the Surface of PbS Nanocrystals: Implications for Incoherent Photon Conversion

Abstract: Ligand-exchange procedures are ubiquitous in the functionalization of colloidal nanocrystals for applications in biological imaging, photocatalysis, and photonic/optoelectronic devices. However, the rich interactions between functional ligands and the nanocrystal surface offer a vast opportunity to achieve emergent self-assembled structures. Here, using 1 H NMR as a probe and L-type-promoted Z-type ligand displacement as a tool to study PbS nanocrystals, we demonstrate that 9-anthracene carboxylic acid (9-ACA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 83 publications
(239 reference statements)
7
39
0
Order By: Relevance
“…NMR characterizations are usually used for QDs in the apolar solvents. In general, the protons of the −CHCH– moiety of OA/OAm are selected for a quantitative study of ligands. , However, in the literature and our own experiments, we found that α-H of the ligands of the binding state also had an obvious NMR signal, which was usually neglected in the past. It has been mentioned in several works that TMEDA would not bind directly onto the nanocrystal surface due to steric hindrance. …”
Section: Resultsmentioning
confidence: 88%
“…NMR characterizations are usually used for QDs in the apolar solvents. In general, the protons of the −CHCH– moiety of OA/OAm are selected for a quantitative study of ligands. , However, in the literature and our own experiments, we found that α-H of the ligands of the binding state also had an obvious NMR signal, which was usually neglected in the past. It has been mentioned in several works that TMEDA would not bind directly onto the nanocrystal surface due to steric hindrance. …”
Section: Resultsmentioning
confidence: 88%
“…It is important to mention that this model oversimplifies the real situation. Intermolecular interactions between surface-functionalized NCs are also influenced by parameters such as the structure of the solvent, , the structure of the ligand shell, or possible sorption–desorption processes of the surface ligands. ,,, Nevertheless, to date this is the best available analytical model that does not require, for example, molecular dynamic simulations, and for the purposes of the current study, it assists in predicting the effect of the different ligands on the overall colloidal stability. As per the developed model, under the studied conditions, the interactions are attractive at interparticle distances ( D IP , distance between NC core surfaces) between 1.7 ± 0.2 nm and 4.0 ± 0.2 nm for the calculated ligand lengths, l , mainly due to the rather low solvation of the ligand shells in toluene (the calculated Flory parameter falls slightly above 0.5, indicating that the free energy of mixing of solvent and ligands is slightly positive).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, their implications during superlattice formation or in the final material’s properties are not yet unambiguously resolved. ,, Recent research has nevertheless greatly expanded the knowledge of the role played by the ligands’ aliphatic chain during self-assembly, highlighting the importance of the ligand shell in mediating superlattice’s formation. ,,,, Moreover, several studies are also shedding light on the influence of the ligands’ functional group. It is emerging that the surface-coordinated species affect: (i) the NC surface, contributing to the overall electronic structure, promoting near-surface restructuring events; ,, (ii) the conformation and position of the ligand molecules on the surface, thus affecting the overall NC organic shell; (iii) the stability of the functionalization; ,, and (iv) the overall reactivity of the NC@ligand . How these NC@ligand specific aspects ultimately impact the SC formation and the final system reactivity, especially when the ligands are used as reactive platforms, is yet to be elucidated.…”
mentioning
confidence: 99%
“…Compared with molecular sensitizers, a QD sensitizer in a TTA-UC system has advantages of the high extinction coefficient and the great flexibility with the wavelength tunability over a wide range of solar spectrum, depending on the size and composition of the QD. , For conversion from NIR, the longest absorption wavelength achieved using molecular sensitizer is 938 nm . For a longer wavelength than that, QDs of the chalcogenide semiconductor (PbS and PbSe) are the only possible choice. , However, only few succeeded to observe the upconverted emission beyond 900 nm, with low upconversion quantum yield (UC-QY). ,, …”
Section: Introductionmentioning
confidence: 99%